Allocation of Authority when a Person is not a Robot - Jianpei Li; Yanhui Wu (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
We formalize a conception of authority, which is commonly defined as the right of controlling a person's actions embedded in human assets in sociology. Due to the inalienable property of human assets, the contractible formal authority is hard to verify and enforce, while real authority usually diverges from formal authority. Inefficiency tends to arise when a task is not routine or can not be done by a robot. Using a framework of incomplete contract, we show that allocation of formal authority, as an instrument to mitigate the inefficiency, is determined by features of tasks and specificity of assets, and the relationship between the resources. Monitoring is then introduced to fine tune value of delegation.
urn:nbn:de:bvb:19-epub-1995-1
Keywords: D23; J24; J41; L22; 330; Transaction of human assets; Real Authority; Formal Authority; Delegation; Monitor; Autorität; Prinzipal-Agent-Theorie; Kooperative Führung; Arbeitsvertrag; Unvollständiger Vertrag; Leistungsbeurteilung; Theorie